2003
DOI: 10.1016/j.biolcel.2003.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial lipopolysaccharide modulates Protein Kinase C signalling in Lymnaea stagnalis haemocytes

Abstract: Our knowledge of cell signalling pathways in the molluscan immune system and their response to immunological challenge is currently poor. The present study focused on the Protein Kinase C (PKC) pathway in the immune cells (haemocytes) of Lymnaea stagnalis and its response following exposure to bacterial lipopolysaccharide (LPS). Western blotting of haemocyte proteins with either anti-PKC (pan) or anti-phospho-PKC (Ser 660) antibodies revealed the presence of two PKC-like immuno-reactive proteins of approximate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 35 publications
3
24
0
Order By: Relevance
“…This was unexpected given the involvement of PKC in both PMA-and laminarininduced H 2 O 2 release by L. stagnalis hemocytes [20] as well as in vertebrate cells as described previously [21]. In addition, the importance of PKC in a variety of molluscan immune-related functions has become increasingly apparent in recent years [23,24]. Perhaps the task PKC carries out in PMA-induced H 2 O 2 release is achieved by a different signaling protein(s) such as PI 3 K or PLA 2 in the BSA-gal induced pathway.…”
Section: Discussionmentioning
confidence: 88%
“…This was unexpected given the involvement of PKC in both PMA-and laminarininduced H 2 O 2 release by L. stagnalis hemocytes [20] as well as in vertebrate cells as described previously [21]. In addition, the importance of PKC in a variety of molluscan immune-related functions has become increasingly apparent in recent years [23,24]. Perhaps the task PKC carries out in PMA-induced H 2 O 2 release is achieved by a different signaling protein(s) such as PI 3 K or PLA 2 in the BSA-gal induced pathway.…”
Section: Discussionmentioning
confidence: 88%
“…Bisindolylmaleimide I and H89 were used at concentrations of 4 and 10 μM, respectively. These doses were used in previous cell-based studies to inhibit PKC and PKA activity (59,60).…”
Section: Lc-ms/msmentioning
confidence: 99%
“…This antibody has previously been validated for use in L. stagnalis haemocytes (Walker and Plows, 2003) and also has been employed to study PKC phosphorylation in M. galloprovincialis haemocytes (Canesi et al, 2005). When L. stagnalis haemocytes were exposed to 10·mg·ml -1 laminarin, a rapid increase in phosphorylation of an 85·kDa PKC likeprotein was observed, with maximum phosphorylation occurring at 10·min (Fig.·1A, upper panel).…”
Section: Laminarin Stimulates the Phosphorylation Of L Stagnalismentioning
confidence: 99%
“…Discussion Current knowledge of cell signalling in molluscs is poor, and much remains to be discovered concerning the specific signalling molecules that regulate defence reactions, triggered by infection, in this important group of organisms. Using the model snail L. stagnalis, we have recently shown that bacterial LPS modulates the phosphorylation (activation) of PKC (Walker and Plows, 2003) and ERK pathway members (Plows et al, 2004) in haemocytes, cells that play a crucial role in the molluscan defence response. The present research aimed to investigate the effects of laminarin on the activation of PKC like-proteins in L. stagnalis haemocytes and to identify some of the upstream regulators and downstream targets of PKC in these cells.…”
Section: Production Of H 2 O 2 By Laminarin-stimulated Haemocytes Ismentioning
confidence: 99%
See 1 more Smart Citation